2021
DOI: 10.48550/arxiv.2111.13847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resource Allocation for IRS-Enabled Secure Multiuser Multi-Carrier Downlink URLLC Systems

Abstract: Secure ultra-reliable low-latency communication (URLLC) has been recently investigated with the fundamental limits of finite block length (FBL) regime in mind. Analysis has revealed that when eavesdroppers outnumber BS antennas or enjoy a more favorable channel condition compared to the legitimate users, base station (BS) transmit power should increase exorbitantly to meet quality of service (QoS) constraints. Channelinduced impairments such as shadowing and/or blockage pose a similar challenge. These practica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The authors showed that the relayassisted networks outperformed direct transmission schemes significantly, though the RIS technology was not the main study topic. Also, [11] studied minimizing the BS transmit power in a RIS-assisted multiple-input-single-output (MISO)-URLLC secure system to design artificial noise, BS beamformer and RIS passive beamforming where the QoS secrecy rate constraint was also taken into account. A CBL allocation, UAV path planning, and transmit power control resource allocation OP was proposed in [12] to facilitate URLLC in UAV-assisted systems utilizing short packets.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that the relayassisted networks outperformed direct transmission schemes significantly, though the RIS technology was not the main study topic. Also, [11] studied minimizing the BS transmit power in a RIS-assisted multiple-input-single-output (MISO)-URLLC secure system to design artificial noise, BS beamformer and RIS passive beamforming where the QoS secrecy rate constraint was also taken into account. A CBL allocation, UAV path planning, and transmit power control resource allocation OP was proposed in [12] to facilitate URLLC in UAV-assisted systems utilizing short packets.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of works have analyzed resource allocation in URLLC systems under FBL regime, e.g., in [6]- [9]. A seminal work in [6] studied a multi-objective approach to maximize the total FBL rate while minimizing the largest target error probability by designing transmit power of BS, and the target error probabilities for users in a noise-limited regime.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that the relayassisted networks outperformed direct transmission schemes significantly, though the RIS technology was not the main study topic. Also, [9] studied minimizing the BS transmit power in a RIS-assisted multiple-input-single-output (MISO)-URLLC secure system to design artificial noise, BS beamformer and RIS passive beamforming where the QoS secrecy rate constraint was also taken into account.…”
Section: Introductionmentioning
confidence: 99%